Strategi Peningkatan Kualitas Sumber Daya Manusia di Baznas Kabupaten Bekasi Dalam Optimalisasi Penyaluran Zakat Mal - Suhrowardi; Iin Masriah; Enur Hotimah; Dede NI; Asih Sugiyanti (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2024)
This study aims to determine the strategy for improving the quality of human resources in BAZNAS Bekasi Regency in optimizing the distribution of zakat mal. Quality human resources are owned by BAZNAS Bekasi Regency, so it is expected that the distribution of zakat mal can be optimized and right on target so that it can change the sustainability of the lives of the Bekasi community, especially the poor and needy. The basis of this study uses a qualitative method. The data sources obtained from this study were through field observations, interviews with the HR staff of BAZNAS Bekasi Regency and mustahik. Other data were obtained by researchers from brochures and the official websites of BAZNAS Pusat and BAZNAS Bekasi Regency. Based on the results of the study, BAZNAS Bekasi Regency has implemented a strategy to form quality resources through various methods including education, training (amil certification), attitudes and behaviors reflected in the BAZNAS law, communication and good relationships between BAZNAS employees and their muzzaki and mustahik. However, the distribution of zakat mal at BAZNAS Bekasi Regency has not reached its maximum, because the type of zakat mal collection at BAZNAS Bekasi Regency is only in professional zakat, infaq and alms.